Geophysical investigation for the detection of liquefaction phenomena in an archaeological site, Lechaion, Greece - Pavlopoulos, Kosmas (2015)
The area of Lechaion located in the northeastern part of the Peloponnese (Greece) is of great archaeological interest because it represents the western harbor of ancient Corinth and includes the remains of an early Christian basilica destroyed during a series of earthquakes in the sixth century AD. Numerous depressions and buckling structures of circular and linear geometry observed on the decorated floor of the basilica are indicative of ground deformation processes possibly related to earthquake-induced ground liquefaction. Electromagnetic (with a conductivity meter), ground penetrating radar (GPR) (with 250 MHz shielded antenna), and electric (ERT) methods have been applied in an effort to study the properties of the substratum and to identify indicative features related to ground liquefaction phenomena. The electromagnetic survey that was used as a reconnaissance method with both coil orientations provided valuable information through data processing, identifying zones of higher conductivity that favor liquefaction, or even the detection of the features themselves. The GPR method detected vertical zones that could represent sand vents either directly with multiple diffractions or indirectly through severe wave attenuation and reduction of the anomaly intensity due to finer sand and increased water saturation. Finally, the ERT method detected layering and the geologic status of the survey area but more importantly, it successfully detected narrow vertical zones of lower resistivity at shallow depths corresponding to sand vents via distinct variations in grain size and permeability. This combination of geophysical methods has successfully detected the dominant trend of east-northeastern-west-southwestern direction and a minor vertical one of north-northwestern-south-southeastern direction of surface depressions caused by liquefaction and generally can successfully provide valuable information on the extent and characteristics of ground liquefaction features in areas of geotechnical or archaeological interest located in regions of intense seismic activity. © 2015 Society of Exploration Geophysicists.